DIGITAL PATHOLOGY IN MELANOMA: ACHIEVEMENTS, BARRIERS AND PROSPECTS - Dudin, O. Ye. (Medical Informatics and Engineering, 2023)
Background. This review is focused on the assessment of the current state of development and implementation of digital pathology in pathologists practice for better diagnostics, counseling, and personalization of melanoma treatment. Materials and methods. The data concerning the digital pathology tools used for melanoma diagnostics and prognostic/ predictive biomarkers assessment were extracted and analysed. Results. The convergence of digital pathology and artificial intelligence has led to a paradigm shift in pathologists' practice. Thanks to digital pathology, pathologists got the opportunity to improve the accuracy, efficiency and consistency of melanoma diagnosis. Access to digital tools with assessing whole slide images facilitated improvement of the remote primary diagnostics, provision of teleconsultations, increased efficiency and balance of workload, improves collaboration between general pathologists and dermatopathologists, flourished virtual education and innovative studies. Detection of sub-visual morphometric features and integration of multi-omics data are prerequisites for improving prognostic and predictive information for personalizing the treatment of melanoma patients, which discovers new prospects for precision medicine. Conclusions. Despite the progress in digital pathology, the implementation of artificial intelligence in diagnostic algorithms of pathologists and personalized treatment requires to solve a number of challenges related to the development and clinical validation of digital tools.